Shipyard bankruptcy policy : a solution in search of a problem - Bodul, Dejan (Array, 2020)
The prevailing approach in mainstream economic theory is that the role of government should be reduced to ensuring an appropriate institutional framework and political stability for the proper functioning of the (free) market. Although the free market concept has proven (at least in theory) to be an unsurpassed mechanism for the effectiveness of economic decision-making and the reconciliation of production and consumption, there are still disputes about the degree of state intervention in the market, which are being re-actualized (in the post-transition and globalization process) when it comes to solving solvency problem(s) in the shipbuilding industry. Although various methodological approaches are available to study such a complex problematic framework, this paper analyzes the legal aspect, since the empirical debates (on some aspects) on the legal regulation of the maritime domain and insolvency proceedings (as well as the ambiguities that have arisen in the application of existing regulations) clearly show which areas and issues need to be urgently addressed and/or reformed.